2007
DOI: 10.1080/03008200701458731
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD1a Negatively Regulates Matrix Metalloproteinase-9 Expression in Mouse FBJ Cell Lines at the Transcriptional Level

Abstract: Mouse FBJ virus-induced osteosarcoma FBJ-S1 cells rich in GD1a are not readily metastatic, whereas FBJ-LL cells with low levels of GD1a are highly metastatic. GD1a was previously shown to suppress metastasis of mouse FBJ cells and to upregulate caveolin-1 and stromal interaction molecule 1 expression. The present study demonstrates that matrix metalloproteinase-9 (MMP-9) expression renders FBJ-LL cells invasive. MMP-9 is inversely regulated by GD1a, based upon four observations: MMP-9 mRNA content was 5 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Zymography-Gelatinase activity was determined according to a previously described method (22). In brief, the conditioned media of cells were collected and mixed with non-reducing sample buffer containing 0.5 M Tris, pH 6.8, 5% SDS, 20% glycerol, and 1% bromphenol blue in a 1:1 ratio and electrophoresed directly on 10% SDS-polyacrylamide gels (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…Zymography-Gelatinase activity was determined according to a previously described method (22). In brief, the conditioned media of cells were collected and mixed with non-reducing sample buffer containing 0.5 M Tris, pH 6.8, 5% SDS, 20% glycerol, and 1% bromphenol blue in a 1:1 ratio and electrophoresed directly on 10% SDS-polyacrylamide gels (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…Expression correlates with metastasis [19] MME Absence associated with metastasis [25] MMP9 Suppression by GD1a decreases metastasis [20] N-Cadherin Overexpression suppresses pulmonary metastasis [24] nm23…”
Section: Lrp5mentioning
confidence: 99%
“…Overexpression of the GD3 synthase gene suppresses MMP-9 expression by inhibiting the combination between the MMP-9 promoter and transcription factors (NF-κB and AP-1) in vascular smooth muscle cells (Moon et al, 2004). In murine FBJ cells, GD1a is found to suppress MMP-9 expression at the transcriptional level (Hu et al, 2007). On the other hand, overexpression of plasma membrane-expressed sialidase Neu3 inhibits MMP-9 expression in vascular smooth muscle cells; implying gangliosides promote MMP-9 (Moon et al, 2007).…”
Section: Gm3 Promotes Cell Motility Via Inducing Matrix Metalloproteimentioning
confidence: 99%
“…These lines of evidence clearly show that PI3K signaling pathway plays an important role in MMP-9 regulation. Reports from several laboratories have concluded that MMP-9 expression is modulated not only by cytokines but also by gangliosides (Hu et al, 2007;Moon et al, 2004;Zhang et al, 2006). GM1, present in the glycolipid-enriched microdomain, is one of the crucial factors regulating cancer metastatic potential via the modulation of MMP-9 localization and secretion, as well as suppression of tumor invasion potential (Zhang et al, 2006).…”
Section: Gm3 Promotes Cell Motility Via Inducing Matrix Metalloproteimentioning
confidence: 99%